Implikasi Pengembangan Ekowisata Kalitalang terhadap Kondisi Sosial Ekonomi Masyarakat Desa Balerante, Kecamatan Kemalang, Kabupaten Klaten - Muhammad, Muhammad; Widarjono, Agus (WELFARE Jurnal Ilmu Ekonomi, 2023)
The tourism sector plays an important role in encouraging economic growth and being one of the sources of foreign exchange earnings. One that is developing and much in demand is tourism with the concept of ecotourism, combining nature conservation, preserving culture, and improving welfare with its economic activities. One of the ecotourism that has natural beauty, cultural potential is Kalitalang Ecotourism, in Balerante village, Klaten Regency. The purpose of this study was to examine the economic impact of the development of Kalitalang ecotourism in Balerante village. This study uses a qualitative approach as well as field studies. The result is that the development of Kalitalang ecotourism has a positive impact on the surrounding community through several ways: first, the opening of opportunities for local MSMEs, second, the development of village infrastructure, and supporting tourist attractions, third, environmental conservation with reduced sand mining, tree cutting, and maintained cleanliness from plastic waste, fourth, increasing Balerante Village tourism branding.Sektor pariwisata berperan penting untuk mendorong pertumbuhan ekonomi serta mampu menjadi sumber penerimaan devisa. Salah satu yang sedang berkembang dan banyak di minati adalah wisata dengan konsep ekowisata, menggabungkan konservasi alam, menjaga budaya, serta meningkatkan kesejahteraan dengan kegiatan ekonominya. Salah satu ekowisata yang memiliki keindahan alam, potensi budaya adalah Ekowisata Kalitalang, di Desa Balerante, Kabupaten Klaten. Penelitian ini bertujuan untuk mengkaji dampak ekonomi dari pengembangan ekowisata Kalitalang di Desa Balerante. Penelitian ini menggunakan pendekatan kualitatif serta studi lapangan. Hasilnya adalah pengembangan ekowisata Kalitalang berdampak positif terhadap masyarakat sekitar melalui beberapa jalan: pertama, terbukanya peluang untuk UMKM lokal. Kedua, pembangunan infrastruktur desa, dan objek wisata pendukungnya. Ketiga, terciptanya konservasi lingkungan dengan berkurangnya penambangan pasir, penebangan pohon, dan terjaga kebersihan dari sampah plastik. Keempat, meningkatnya branding wisata Desa Balerante.